Legal Conditioning of Public Offers to Buy Shares - Jebur, Jaafar Kadhim (Journal of Ecohumanism, 2024)
Public shares purchase offerings are made by the person publicly notifies the shareholders of the target company of the acquisition that he has a desire to acquire the shares they own in the company at a specified price in cash or by exchanging shares for shares, note that these public offers are made from shares that form part of the capital and gives the right to vote on the decisions issued by the company’s board of directors. This means that the public shares purchase offerings is the acquisition and control over the board of directors of a particular company and the decisions it issues.